Sistem informasi adminisrasi puskesmas Gamping 1 Sleman - Suroto (FTI 15 UMY 144, 2015)
*144 Public and Specialist Polyclinic GAMPING 1 is a business that specializes in healthcare to serve the community of Gamping, Sleman and surrounding areas. However, in this business, Public and Specialist Polyclinic GAMPING 1 is still having trouble because the manual recording and not elegant, so that the performance is less effective and efficient, making the line long and would be resulted on the length of service time in the Administration. The number of patients who come with their families make the level of the crowd people lead to difficult situation for Public and Specialist Polyclinic GAMPING 1 to provide drugs services and managing transactions in an efficient way. Using software NetBeans IDE 7.1.2 and 1.7.4 Xamppwin32 I created a Desktop app for managing patients, medicine, doctors and nurses and the documents contained in the Public and Specialist Polyclinic GAMPING 1. This application is expected to help Public and Specialist Polyclinic GAMPING 1 so the performance can run fast, and accurate, and the information obtained is useful for the progress of services to patients.